KUALITAS PELAYANAN VISA KUNJUNGAN DI KANTOR IMIGRASI PEKANBARU - Arlieza Anggi Desty; Firdaus Yusrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
In encouraging economic development, the government has rolled out policies that support economic development in all lines, including in the field of immigration. One of the policies is free visa approval. Visits to state people, state-specific regional governments, and certain entities with hopes of this policy can increase the number of foreign tourist visits in particular. This research was conducted to study the method of visa issuance and the quality of visa visit services at the Pekanbaru City Immigration Office by using quantitative descriptive methods to examine the contradictions carried out by analyzing tourist recommendations regarding Visa Visit services at the Pekanbaru City Immigration Office. The questionnaires distributed amounted to 100 people. While the data collection techniques in this study used observation, questionnaires, and documentation. Research variables are tangible, responsiveness, reliability, assurane, empathy.Keywords :Quality of Service, Visit Visa, Immigration Office